Сontraction and expansion of the Turkic lexicon borrowed in the Arabic language - Alzhanbaeva, U. T. (Journal of Oriental Studies, 2016)
This article discusses the contraction and expansion of the semantic fields of the Turkic lexicon borrowed in the Arabic language, reveals the causes of this phenomenon.